2021
DOI: 10.3390/molecules26020385
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Curable Solvent-Free Acrylic Pressure-Sensitive Adhesives via Photoredox-Mediated Radical Polymerization

Abstract: Owing to their excellent properties, such as transparency, resistance to oxidation, and high adhesivity, acrylic pressure-sensitive adhesives (PSAs) are widely used. Recently, solvent-free acrylic PSAs, which are typically prepared via photopolymerization, have attracted increasing attention because of the current strict environmental regulations. UV light is commonly used as an excitation source for photopolymerization, whereas visible light, which is safer for humans, is rarely utilized. In this study, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Because the redox potentials of initiators could reflect their ability of electron acceptance in the catalytic cycle, we investigated the half‐peak potential [19] of TsCl by cyclic voltammetry (CV). Compared to diethyl 2‐bromo‐2‐methylmalonate, ethyl‐bromoisobutyrate and ethyl 2‐bromopropionate ( E p/2 =−0.75 to −0.85 V vs. SCE), [4c, 20] TsCl exhibits a more negative half‐peak potential ( E p/2 =−0.98 V vs. SCE), suggesting that the alkyl bromides are easier of being reduced to generate active carbon radicals in the photoredox‐mediated O‐ATRP as realized in many examples, [4a–e] and meanwhile implying that sulfonyl chlorides are more difficult initiators in terms of electron acceptance.…”
Section: Resultsmentioning
confidence: 99%
“…Because the redox potentials of initiators could reflect their ability of electron acceptance in the catalytic cycle, we investigated the half‐peak potential [19] of TsCl by cyclic voltammetry (CV). Compared to diethyl 2‐bromo‐2‐methylmalonate, ethyl‐bromoisobutyrate and ethyl 2‐bromopropionate ( E p/2 =−0.75 to −0.85 V vs. SCE), [4c, 20] TsCl exhibits a more negative half‐peak potential ( E p/2 =−0.98 V vs. SCE), suggesting that the alkyl bromides are easier of being reduced to generate active carbon radicals in the photoredox‐mediated O‐ATRP as realized in many examples, [4a–e] and meanwhile implying that sulfonyl chlorides are more difficult initiators in terms of electron acceptance.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve this, water‐soluble and weakly electron‐donating sulfonate moiety was introduced in one of four donor groups of "4DP‐IPN" with a strongly twisted donor–acceptor structure that has been known for highly efficient organic PC for various organic reactions and polymerizations. [ 43–51 ] Most excitingly, the discovered PC exhibited unique “oxygen‐acceleration” behavior in PET‐RAFT polymerizations of a variety of acrylates and acrylamides in both DMSO and aqueous conditions without any additives, which is apparently distinct from previously reported systems. [ 30,31 ] Combined experimental and theoretical studies suggested that molecular oxygen acts as an electron shuttle to catalyze the electron transfer between the PC in the excited state and the chain‐transfer agent (CTA) (Figure 1d).…”
Section: Introductionmentioning
confidence: 92%
“…Increasingly, in the last decade, publications on ecological methods of PSAs preparation have been made, of which the most important are photopolymerization processes. Back et al reported on a new pro-ecological method of obtaining solvent-free PSAs via visible-light-driven photocatalytic radical polymerization [ 10 ] and photoredox-mediated radical polymerization [ 11 ]. Instead, Beak at al.…”
Section: Introductionmentioning
confidence: 99%